An Efficient Safety System For Vanet Using Enhanced Message Dissemination Protocols With Channel Performance Control - Samara, Ghassan Abedalkarim Abdullah (2012)
The rapid development of wireless communication networks in recent years has made vehicle to vehicle (V2V) and vehicle to infrastructure (V2I) communications possible in mobile ad hoc networks (MANETs). It has also led to the development of a new technology called vehicular ad hoc network (VANET), which aims to achieve road safety, infotainment, and a comfortable driving experience. It can support safety systems designed to avoid road accidents in two ways: 1) periodic transmissions (beacon) from all vehicles that inform neighbors about their current status, and 2) dissemination of emergency messages to warn other vehicles to avoid the danger.